Efektivitas Penerapan Model Pembelajaran Collaborative Learning Untuk Meningkatkan Keaktifan Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam Di Madrasah Aliyah Nahdlatul Athfal Gersempal Omben Sampang - Ach Baihaqi; Khairun Nisa'; Imam Wahli; Achmad Rauhul Abror; Moh Farid (Institut Kariman Wirayudha Sumenep, 2022)
This research was motivated by students' lack of interest in the subject of Islamic Cultural History, resulting in boredom and a lack of active participation. The primary objective of this study was to determine the extent to which this learning model can increase student engagement and to demonstrate positive changes in student understanding and participation in the learning process. The research focused on two main topics: first, how effective is the implementation of the Collaborative Learning model in increasing student engagement in the subject of Islamic Cultural History at Madrasah Aliyah Nahdlatul Athfal; and second, what are the supporting and inhibiting factors in the effectiveness of the implementation of the Collaborative Learning model in increasing student engagement.In this thesis, the author used a qualitative approach. The rationale for using a qualitative approach was to facilitate the researcher in obtaining research results from the field, both verbally and in writing, regarding the situations and conditions experienced by students during the teaching and learning process. The results showed that the implementation of the Collaborative Learning model was effective in increasing student engagement. This was evidenced by students' enthusiasm in group discussions, their courage to express their opinions, their increased confidence, and their increased understanding of the Islamic Cultural History material. Supporting factors for the successful implementation of this model were students' high enthusiasm for learning, teacher readiness and creativity, and a conducive learning environment. Meanwhile, inhibiting factors included unequal roles within groups and a lack of understanding of the material among some students. These findings are expected to provide input for teachers and prospective teachers in selecting and implementing appropriate learning models to increase student engagement.